2006
DOI: 10.1063/1.2186393
|View full text |Cite
|
Sign up to set email alerts
|

Crack detection and analyses using resonance ultrasonic vibrations in full-size crystalline silicon wafers

Abstract: An experimental approach for fast crack detection and length determination in full-size solar-grade crystalline silicon wafers using a resonance ultrasonic vibrations (RUV) technique is presented. The RUV method is based on excitation of the longitudinal ultrasonic vibrations in full-size wafers. Using an external piezoelectric transducer combined with a high sensitivity ultrasonic probe and computer controlled data acquisition system, real-time frequency response analysis can be accomplished. On a set of iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…The transducer contains a central hole allowing a reliable vacuum coupling between the wafer and transducer by applying 50-kPa negative pressure to the backside of the wafer. Belyaev et al [67] reported that for C-Si wafers, the increased crack length leads to decrease in peak frequency and increase in peak bandwidth. A typical RUV system can detect cracks up to submillimeter lengths.…”
Section: E Resonance Ultrasonic Vibrationmentioning
confidence: 98%
See 1 more Smart Citation
“…The transducer contains a central hole allowing a reliable vacuum coupling between the wafer and transducer by applying 50-kPa negative pressure to the backside of the wafer. Belyaev et al [67] reported that for C-Si wafers, the increased crack length leads to decrease in peak frequency and increase in peak bandwidth. A typical RUV system can detect cracks up to submillimeter lengths.…”
Section: E Resonance Ultrasonic Vibrationmentioning
confidence: 98%
“…The resonance ultrasonic vibrations (RUV) technique developed by Belyaev et al [67] is used for fast microcrack detection in solar grade crystalline silicon wafers. In this method, ultrasonic vibrations of a tunable frequency and adjustable amplitude are applied to the silicon wafer using an external piezoelectric transducer in the frequency range of 20-90 kHz.…”
Section: E Resonance Ultrasonic Vibrationmentioning
confidence: 99%
“…In the past, various specialised tools and instruments have been developed to solve this problem. Some recent techniques include light beam induced current (LBIC) [7], lock-in thermography (LIT) [8], resonance ultrasonic vibration (RUV) [9], scanning acoustic microscopy (SAM) [10], electroluminescence (EL) [11][12][13][14][15], photoluminescence (PL) [16][17][18][19][20] and optical transmission (OT) [21][22][23][24][25]. Good topical reviews on these subjects have been published elsewhere [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Several state-of-the-arts methods have been proposed widely in order to detect solar cells micro cracks; resonance ultrasonic vibrations (RUV) method for crack detection in PV silicon wafers has been firstly proposed by [1] and [2]. This detection method uses ultrasonic waves of a plausible frequency though a transducer operating on a range of 20 to 90 kHz.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence (PL) detection method was firstly eveloped to enhance the detection of solar cells micro cracks. This technique can be used to detect micro cracks in silicon wafers as well as in large-scale PV panels [3]. PL technique could be cast-off not only at the end of the production process of solar cells but also it is commonly situated in the interior process of production line [4].…”
Section: Introductionmentioning
confidence: 99%